Increasing importance of social services in the times of demographic challenge - Krzyszkowski, Jerzy (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The paper is the presentation of social services, especially care services as the subject that rarely present in Polish literature on social policy even in the times of demographic challenge. The main issues analyzed discussed in the article are: history and current situation of care services in Europe and Poland. In conclusions some recommendations for social policy practice are formulated.